Implementasi Aliran Filsafat Progresivisme Dalam Pendidikan Karakter di SMK IT Al Husna Lebong - Ferti, Ferti silviana lianvani; Deriwanto, Deriwanto (Yayasan Literasi Kita Indonesia, 2023)
Philosophi of education is an effort in the search for rights in the field of education and knowledge. The philosophy of education can also be used in realizing the ideals of education and become a reference in its implementation in education. Progressivism is a flow between the scoohls of education philosophy. The flow of progressivism philosophy emphasizes change or progress and experiences to solve student problems in SMK IT AL Husna Lebong. This stream is focused on student rather than teachers. The folow of progressivism philosophy is the basic and foundation in creather education. In this case, it is hoped that character education can be useful for student in their lives, especially in solving a problem. Cultivation of character education can be done through the environment of teachers, parents, and the community. So tat environment becomes an exa,ple and role model for student. This study uses a literature review research method by searching in the form of books and journals.